PENGARUH PERTUMBUHAN INVESTASI, PERTUMBUHAN PENYERAPAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DAN PERUBAHAN STRUKTUR EKONOMI DI PROVINSI BALI - novena, mariana; Utama, Made Suyana; Purbadharmaja, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
Normal 0 false false false EN-US X-NONE X-NONE The Investment plays a central role in increasing employment opportunities and economic growth as well as an impact on changes in the economic structure. This study aimed to analyze the effect of investment growth and employment growth to economic growth and changes in the economic structure of the province of Bali from 1985 until 2012. The data used are secondary data obtained from the Central Statistics Agency of Bali and other related agencies . The analysis technique used is path analysis and descriptive analysis . This study concluded that from 1985 to 2012 investment growth and a significant positive effect on employment growth and economic growth. Employment growth and a significant positive effect on economic growth. Growth of investment and employment growth does not significantly influence changes in the economic structure. Economic growth is positive and significant effect on the changes in the economic structure. Growth investing significant effect on economic growth through employment growth in the province of Bali. Investment growth significantly influence the economy through changes in the structure of economic growth in the province of Bali. Employment growth significantly influence the economy through changes in the structure of economic growth in the province of Bali . There is significant growth in investment , employment growth and economic growth to changes in the economic structure directly or indirectly indicate that necessary to study the pattern of investment to spur employment growth and economic growth in accordance with the economic structure to be implemented in Bali province , so that changes in the structure of the economy can be controlled.
Keywords: Investment Growth , Growth Employment Absorption , Economic Growth and Structural Changes in Economics.